Study quality and neutralization of rainwater - Kam, Yuen Yuk (2014)
This thesis has discussed about the quality and neutralization of rainwater samples from Semenyih in Selangor and also Gambang area in Pahang. The rainwater samples were compared based on their physicochemical characteristics and neutralization factor in both areas. The physicöchemicaL parameters that were conducted included pH, temperature, biochemical oxygen demand (BOD), chemical oxygen demand (COD), hardness, total suspended solid (TSS), total dissolves solid (TDS), electric conductivity, turbidity, selected heavy metal concentration and ionic concentration. The objectives of the study were to determine the physicochemical characteristics of the rainwater in the study area and also to investigate the neutralization potential of the rainwater for agricultural and domestic purposes. The used method for all the physicochemical parameters was according to the APHA and HACH standard. Based on the result taken, the pH value of the rainwater that obtained from Semenyih area showed that it was 4.24 and 4.40 which indicates as acidic rain (pH<5.6) based on two samples taken. The concentration of Ca 2 ranged from 0.10 to 0.13 mg/L while for the concentration of Mg 2+ varied from 1.26 to 1.44 mg/L. The electrical conductivity varied from 122 to 338 J1 5 /cm while the total hardness ranged from 1.36 to 1.57 mgIL CaCO 3 . For the rainwater at Gambang area, the pH was 8.50 and 8.63 which was considered as alkaline rain by considering 5.6 as the neutral pH of cloud water with atmospheric CO 2 equilibrium. The concentration of Ca 2 varied from 1.09 to 1.48 mg/L while for the concentration of Mg 2+ ranged from 0.59 to 1.96 mg/L. The electrical conductivity varied from 239 to 325 9 5 /cm while the total hardness ranged from 2.07 to 3.05 mg/L CaCO3. From the results it also showed that Semenyih area major neutralization factor was on NFL that caused by NH3 emission at agricultural (urea application) activities and intensive animal production facilities while for the Gambang area, Ca 2 was the major neutralizing agent that might be caused by the dust-rich local and surrounding limestone environment. For the future research, it is recommended that the research should be conducted at least ten days and the number of samples that should be taken must be more than five at each location so that a more accurate readings and conclusion could be made based on the extra results that have been taken.